(untitled) (Melayu: Jurnal Antarabangsa Dunia Melayu, 2020)
This article is a study of the history, customs and heritage of the indigenous Jahut tribe. An ethnographic approach was used for this study to explain descriptively the culture and sub-culture of the Jahut in Kampung Kuala Krau in the state of Pahang. Based on data from the profile of indigenous villages in the Temerloh district in 2009/2010, the ethnic Jahut in this village number 702 people. From this number, seven informants were selected. The method employed for this research was structured interviews, observations and recordings. The findings of this study constitute a record of the beliefs, customs, healing practices and taboos of the Jahut community in the area under study. Being a minority, their culture and identity are under threat with the passage of time. Therefore, this article is an effort to document the existence of this community. Keywords: history, customs, heritage, beliefs, Jahut indigenous people